Determinants of Customers E-Payment Utilization in Commercial Bank of Ethiopia the Case of Nekemte Town - Gofe, Tesfaye Eresso; Tulu, Dereje Regasa (Journal of Asian Business Strategy, 2019)
The study was intended to analyze the determinants of customers E-payment utilization in the Commercial Bank of Ethiopia Nekemte town. To achieve the objectives, both primary and secondary data were collected from the selected samples. The collected data were analyzed by employing descriptive statistics and ordered logit model by using STATA software version 12. The major finding of the study shows that among the demographic related factors customer’s education and income level has positively influenced their E-payment Utilization activities, Whereas among the institutional related factors the network interruption and service charge levied by the bank has a negative influence while the customer satisfaction and cost reduction concern has a positive influence on their E-payment Utilization activities. Lastly, among the customer related factors both perceived risk and lack of willingness to use the service has a negative influence on their E-payment utilization activities in the study area. Based on the result, the authors recommended that the institution has to seriously focus on the improvement of frequent quality service delivery in its daily operations that encourage their E-payment utilization activities and the branch supervisors has to deal with the concerned body on the network interruption and service charge levied by the bank in order to facilitate the smooth functioning of customers E-payment utilization activities.